Comparative Analyses of Full-Length Transcriptomes Reveal Gnetum luofuense Stem Developmental Dynamics - Hou, Chen; Lian, Huiming; Cai, Yanling; Wang, Yingli; Liang, Dongcheng; He, Boxiang (Frontiers in Genetics, 2021)
Genus Gnetum, of which the majority species are pantropical liana, have broad industrial uses 18 including for string, nets, and paper production. Although numerous studies have investigated 19 anatomical structures during stem development, the underlying molecular mechanisms that regulate 20 this developmental trajectory in Gnetum species remain poorly understood. A total of 12 full-length 21 transcriptomes were generated from four stem developmental stages of an arborescent representative 22 of this genus, G. luofuense, using Oxford Nanopore Technologies (ONT). The results of this analysis 23 reveal a total of 24,151 alternative splicing (AS) and 134,391 alternative polyadenylation (APA) 24 events. A remarkably dynamic pattern of AS events, especially in the case of intron retentions, was 25 found across the four developmental stages while no dynamic pattern was found among transcript 26 numbers with varied poly(A) sites. A total of 728 long non-coding RNAs (lncRNAs) were also 27 detected; the number of cis-regulated target genes dramatically increased while no changes were 28 found among trans-regulated target genes. In addition, a K-mean clustering analysis of all full-length 29 transcripts revealed that primary growth is associated with carbohydrate metabolism and fungi 30 defense, while secondary growth is closely linked with photosynthesis, nitrogen transportation, and 31 leaf ontogenesis. The use of weighted gene co-expression network analysis as well as deferentially 32 expressed transcripts (DETs) reveals that bHLH, GRF, and MYB-related transcription factors are 33 involved in primary growth, while AP2/ERF, MYB, NAC, PLAZ, and bZIP participate in G. 34 luofuense stem secondary growth. The results of this study provide further evidence that Nanopore 35 sequencing technology provides a cost-effective method for generating full-length transcriptome data 36 as well as for investigating seed plant organ development.